Analysis of the Financial Performance of the Local Government of Tebo Jambi Regency using the Value for Money Method (2018-2022 Fiscal Year) - A.M. Furqon; Iskandar Sam; Wiwik Tiswiyanti (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to analyze the financial condition by assessing the financial performance of the Regional Government of Tebo Regency. The data used in this study is secondary data sourced from reports on the realization of the Tebo Regency local government budget for the period 2018 to 2022. The ratio analysis used in this study is: 1) Economic Ratio, 2) Efficiency Ratio, 3) Effectiveness Ratio. The results of the study show the performance of the Regional Government of Tebo Regency for the 2018-2022 fiscal year in Economic Ratio including economic criteria, the performance of the Regional Government of Tebo Regency for the 2018-2022 fiscal year in Efficiency Ratio including inefficient criteria, the performance of the Local Government of Tebo Regency for the 2018-2022 fiscal year in Ratio Effectiveness including very effective category